Effect of strontium substitution on structure and reduction property of LaCoO3 perovskite catalyst - Ao, Min; Pham, Gia Hung; Sage, Valerie; Pareek, Vishnu (2014)
Fischer–Tropsch (F-T) technology is a promising candidate for the conversion of syngas to valuable synthetic fuels. Perovskite-type oxides, particularly LaCoO3 have extensively been investigated in F-T synthesis as they demonstrate chemical and thermal stability at high temperatures as well as excellent redox properties. Compared to standard cobalt-alumina FT catalysts, perovskite catalysts have highly versatile and widespread mineral form that can lead to several desired physical and chemical properties. This paper presents the effect of partial substitution of La3+ by Sr2+ in LaCoO3 perovskites. We found that the substitution affected the structure and redox property of the catalyst, and is expected to further affect the catalyst activity (CO conversion) in F-T synthesis for higher alcohol production. A series of La1-xSrxCoO3 catalysts, in which x=0, 0.05, 0.1 0.2 and 0.3, was synthesised through co-precipitation methods and calcined at 800 C. The catalysts were characterized by X-ray diffraction (XRD), temperature-programmed reduction (H2-TPR) and temperature-programmed oxidation (O2-TPO) techniques. The XRD analysis confirmed the maximum amount of Sr2+ to substitute of La3+ is x=0.3. Beyond this limit, the catalysts do not show a perovskite-type structure. In H2-TPR profiles, when the amount of Sr2+(x) increased, there was an increase in the number of reduction peaks and their area. It is thought that oxygen vacancies resulting from Sr2+ substitution plays an important role in the catalysts redox properties.